Novel techniques to quantitatively assess age-dependent alterations in biophysical properties of HSPCs and bone marrow niche - Ho, Anthony Dick; Tanaka, Motomu (Experimental hematology, 2025)
The present knowledge on hematopoietic stem and progenitor cell (HSPC) biology and aging is based largely on studies in mouse models. Although mouse models are invaluable, they are not without limitations for defining how physical properties of HSPCs and their niche change with age. The bone marrow (BM) niche is a complex, interactive environment with multiple cell types. The structure and organization of the BM niche, especially the extracellular matrix (ECM), change with age. Provided with recent advances in quantitative analytical techniques and in vitro niche models, we have developed novel tools to quantitatively assess the impact of specific biochemical and physical cues on homing, adhesion, and migration of HSPCs. Recent developments in in vitro niche models have also provided new insights into the interactions between HSPCs and their niche, particularly the role of matrix stiffness. Further research is needed to integrate physical biomarkers into comprehensive mathematical models of age-dependent HSPC-niche interactions. The key is to use mouse models in conjunction with direct analyses in in vitro niche models to achieve a more comprehensive understanding of age-dependent alterations in niche function and regulation.